Nitrogen Gain and Loss Along an Ecosystem Sequence: From Semi-desert to Rainforest - Abdallah, Khaled; Stock, Svenja C.; Heeger, Felix; Koester, Moritz; Nájera, Francisco; Matus, Francisco; Merino, Carolina; Spielvogel, Sandra; Gorbushina, Anna A.; Kuzyakov, Yakov; Dippold, Michaela A. (Frontiers in Soil Science, 2022)
Plants and microorganisms, besides the climate, drive nitrogen (N) cycling in ecosystems. Our objective was to investigate N losses and N acquisition strategies along a unique ecosystem-sequence (ecosequence) ranging from arid shrubland through Mediterranean woodland to temperate rainforest. These ecosystems differ in mean annual precipitation, mean annual temperate, and vegetation cover, but developed on similar granitoid soil parent material, were addressed using a combination of molecular biology and soil biogeochemical tools. Soil N and carbon (C) contents, δ15N signatures, activities of N acquiring extracellular enzymes as well as the abundance of soil bacteria and fungi, and diazotrophs in bulk topsoil and rhizosphere were determined. Relative fungal abundance in the rhizosphere was higher under woodland and forest than under shrubland. This indicates toward plants' higher C investment into fungi in the Mediterranean and temperate rainforest sites than in the arid site. Fungi are likely to decompose lignified forest litter for efficient recycling of litter-derived N and further nutrients. Rhizosphere—a hotspot for the N fixation—was enriched in diazotrophs (factor 8 to 16 in comparison to bulk topsoil) emphasizing the general importance of root/microbe association in N cycle. These results show that the temperate rainforest is an N acquiring ecosystem, whereas N in the arid shrubland is strongly recycled. Simultaneously, the strongest 15N enrichment with decreasing N content with depth was detected in the Mediterranean woodland, indicating that N mineralization and loss is highest (and likely the fastest) in the woodland across the continental transect. Higher relative aminopeptidase activities in the woodland than in the forest enabled a fast N mineralization. Relative aminopeptidase activities were highest in the arid shrubland. The highest absolute chitinase activities were observed in the forest. This likely demonstrates that (a) plants and microorganisms in the arid shrubland invest largely into mobilization and reutilization of organically bound N by exoenzymes, and (b) that the ecosystem N nutrition shifts from a peptide-based N in the arid shrubland to a peptide- and chitin-based N nutrition in the temperate rainforest, where the high N demand is complemented by intensive N fixation in the rhizosphere.